Braiding Our Lives: Black Immigrant Mothers and Adult Literacy - Fearon, Stephanie (The Canadian Journal for the Study of Adult Education / La revue canadienne pour l’étude de l’éducation des adultes)

(untitled) (Canadian Association for the Study of Adult Education / L’Association canadienne pour l’étude de l’éducation des adultes, 2022)
Adult literacy is a pressing policy issue in Canada. Reports reveal immigrant communities as accounting for a relatively large share of the country’s population experiencing low reading, writing, numeracy, and information processing skills. This paper explores how Black immigrant women who are adult literacy learners negotiate and reconfigure their motherwork while living abroad in Toronto with their families. This article presents insights obtained from six in-depth interviews with African Caribbean mothers living in Toronto. In these interviews, participants shared stories that centre the following questions: What are the literacy experiences of Black immigrant mothers who are adult learners? How can we better support their literacy journey?Drawing on an arts-informed narrative methodology, this study compiled findings gained from interviews into the creative non-fiction story Braiding Our Lives. Braiding Our Lives captures personal narratives, shared by study participants, highlighting the central role of homeplace and cultural work in the lives of Black immigrant mothers who are literacy learners.